Lara Croft and the Guardian of Light. - Davison, John.
Tomb Raider is dead. Long live to new Tomb Raider. Lara Croft gets a gameplay makeover and moves toward a fully digitally distributed future.
Keywords: Crystal Dynamics (Firm); Croft, Lara (Fictitious character); Tomb raider; Three-dimensional imaging; 3D games